Edukasi postnatal dengan pendekatan family centered maternity care (FCMC) / Diyan Indriyani, Asmuji, NS. Sri Wahyuni. - DIYAN INDRIYANI; Asmuji; Sri Wahyuni, NS. (Trans Medeika, 2016)
xiv, 170 hlm. : ilus. ; 23 cm